Application of an acoustic wave sensor for copper quantification in the water and particulate matter of the Ria de Aveiro - Yamasaki, A. (2015)
Copper is one of the most studied metals and its concentration in estuaries is of great concern, due to its possible toxic effect, as well as to its nutritional importance at low concentrations. A quartz crystal resonator can be used to quantify metals, but it needs to be combined with an electrochemical pre-concentration step to detect low copper concentrations [ 1 ] . Cathodic deposition of the metal at the gold electrodes of a quartz crystal for a period of 3 minutes allowed detecting copper in solutions at concentrations as low as 1.46 μ g L -1 , by measuring the frequency of oscillation of the crystal itself. This methodology was used to determine dissolved copper and “particulate copper” (copper content in the particulate matter) in samples from a channel which connects an estuary (Ria de Aveiro) to the ocean (Atlantic Ocean). The samples were collected at the centre of the channel at the surface and bottom, and at the surface in its Northern bank. Tidal influence was assessed by sampling during summer, at neap and spring tides. Samples were always collected at low tide, flood and high tide. It is known that hydrodynamics and physicochem ical characteristics of the water affect metal transport and its partition between water column, particulate and sediments. Salinity, pH and dissolved oxygen were always measured along with copper. A gradient in salinity was observed from the surface towards the bottom, and copper concentration, both dissolved and particulate, increased along depth, probably because water turbulence remobilizes the metal from sediment. Possible inputs from the ocean are still under evaluation. During neap tide and low water, the behaviour is the opposite, and concentrations are lower at the bottom, where salinity is higher. Near the banks, at surface, copper content is lower than in the centre of the channel. The analytical methodology did not allow the determination of labile copper, as the levels were bellow the detection limit. However, the application of a piezoelectric quartz crystal to follow native bacterial growth in the water of the lagoon [ 2 ] had already shown that no toxic effects could be detected at copper concentrations in the range of the total copper contents found in the present work